Recent developments and new direction in soft-computing foundations and applications : selected papers from the 4th World Conference on Soft Computing, May 25-27, 2014, Berkeley /: selected papers from the 4th World Conference on Soft Computing, May 25-27, 2014, Berkeley. (2016) - Unknown
No abstract available